Gambaran Health Literacy dan Health Seeking Behaviour pada Pasien ISPA di Puskesmas Bangetayu Semarang - Siti Rohmah; Ahmad Ikhlasul Amal; Erna Melastuti (STIKes Ibnu Sina Ajibarang, 2025)
Acute Respiratory Infection (ARI) is a condition that affects the human respiratory system. ARI can be caused by various types of pathogens, including viruses, bacteria and fungi. This condition can cause symptoms such as runny nose, shortness of breath, coughing, and fever, and has the potential to develop into more serious complications if not treated properly. This study aims to determine the description of health literacy and treatment seeking behavior in ARI patients. The research uses quantitative methods with a cross-sectional approach. The sample for this study was ISPA patients who visited the Bangetayu Semarang Community Health Center. Data collection was carried out through a structured questionnaire that measured the level of health literacy and health seeking behavior patterns of respondents. The research results obtained from respondents with the youngest age category being 19 years old and the oldest being 69 years old, the dominant gender being female, 66 respondents with a percentage of (55.5), the dominant education level being SMA/SMK, 76 respondents (63.9%), and the dominant income figure. enough, namely 110 respondents (92.4%). 2. Most of the respondents' health literacy was good with 74 respondents (66.3%) and the lowest were respondents with problematic health literacy, namely 5 respondents (4.2%). Most of the respondents did not support health seeking behavior with 91 respondents (76.5%) and the rest There were 28 respondents(23.5%)whosupported health seeking behavior.